2007
DOI: 10.1002/ijc.22590
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of glutathione‐S‐transferase M1 and manganese superoxide dismutase are associated with the risk of malignant pleural mesothelioma

Abstract: Individual response to oxidative stress, due to exposure to asbestos fibres plays a significant role in the malignant pleural mesothelioma (MPM) etiology. The differential impact on MPM risk of polymorphic alleles of glutathione-S-transferases (GSTs) and manganese superoxide dismutase (MnSOD/SOD2) genes involved in the defence against oxidative damage has been investigated. Ninety cases of MPM and 395 controls were genotyped using the arrayed-primer extension technique. Logistic regression analysis was applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 38 publications
6
49
2
Order By: Relevance
“…MAF values obtained were in accordance with the ones reported in the HapMap project (http://www.hapmap.org/). The data available in the literature in Caucasian populations, the genotype frequencies for the GSTA2 S112T polymorphism and the values reported in these studies are ambiguous, two of them are in agreement with the data obtained in this study (16,29), while further two studies report different frequencies (17,30). The SNP frequencies in control and cancer population are not significantly different and the crude and adjusted ORs associated with each polymorphism are not significantly different (Table III), suggesting that these polymorphisms are not associated with breast cancer susceptibility.…”
Section: Resultssupporting
confidence: 88%
“…MAF values obtained were in accordance with the ones reported in the HapMap project (http://www.hapmap.org/). The data available in the literature in Caucasian populations, the genotype frequencies for the GSTA2 S112T polymorphism and the values reported in these studies are ambiguous, two of them are in agreement with the data obtained in this study (16,29), while further two studies report different frequencies (17,30). The SNP frequencies in control and cancer population are not significantly different and the crude and adjusted ORs associated with each polymorphism are not significantly different (Table III), suggesting that these polymorphisms are not associated with breast cancer susceptibility.…”
Section: Resultssupporting
confidence: 88%
“…Some of the studied DNA repair genes revealed significant associations, but most of them disappeared after Bonferroni correction for multiple analyses. A further study from the same group reported an association with SOD2 16A [34].…”
Section: Discussionmentioning
confidence: 83%
“…Since several of the SNPs that were studied in this work were the object of two previous papers [33,34], we also carried out a meta-analysis. Gemignani et al [33] used two panels of controls: panel 1 included individuals whose asbestos exposure was known, whereas panel 2 included blood donors whose asbestos exposure had not been evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The endpoints measured in these studies included: levels of circulating proteins (HER-2/neu, mesothelin, osteopontin, mutated K-ras), growth factors (PDGF-AB, HGF, EGF, SCF) or antibodies (anti-p53), erythrocyte glycophorin-A variants, DNA adducts, micronuclei, DNA repair activities, SV40, single-nucleotide polymorphisms in metabolic, DNA repair or other genes, and microRNA. A list of published studies has been previously reported (7), while most recent publications have been added to the references (19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%